Peranan Pengusaha Industri Tekstil dalam Pelaksanaan Program Kali Bersih (Prokasih) di Daerah Aliran Bengawan Solo Surakarta - Sri Rahayu Purwani Djati (Exsplorasi, 2009)
ABSTARCT This research was held in Surakarta involving four textile manufacturers which potentially produce dangerous wastes contaminating Bengawan Solo river. By the implementation of Program Kali Bersih (Prokasih) based on Meyer Of Surakarta Decree No. 550.1/127/1/1998 and Natural environment Primary Act 23/1997, there expected the participation of textile manufacturer industries in their capability to reduce the impact of water contamination. This research was descriptive analytic with the aims was to gain te holistic and systematic description about the participation of textile manufactures in implementing Prokasih program. Using juridical normative approach, data were collected throught library study and field study. The manufacturer samples are taken in purposive sampling (selected in certain characteristics basis). The interview with key respondents was held with interview guide. The used data analysis was qualitative analysis for the variables which related with region and company profile, while for laboratory test, there used common tables. The result being reacged in Prokasih is that the water condition in Bengawan Solo River is increasingly better, which formerly containing many of ammonia, copper, sulfide, cadmium and black lead, for presently, there only remains the cadmium.   Keyword : Textile, industry, dangerous waste, Program Kali Bersih, Bengawan Solo